THE RESULTS OF A FIELD STUDY ON THE EVALUATION OF COMPREHENSIVE ASSISSTANCE TO WOMEN AND CHILDREN RETURNED FROM THE MILITARY ZONES IN THE FRAMEWORK OF STATE REINTEGRATION PROGRAMS - Yuldashev Sanjar Ruzimurodovich (EPRA International Journal of Research and Development (IJRD), 2022)
Armed forces in Syria between the government and ISIS illegal paramilitary groups attempting to create a new Islamic state, thanks to the successful dissemination of their radical extremist ideologies among the communities and people who are professionals of Islam, have led to active recruitment as well as joining to their ranks of individuals who have expressed a desire to help their viewpoints. Recruitment and involvement in military teams, although prevailing among men, has also not left aside women as well as children, who are also target groups for the implementation of long-term military strategies of ISIS. Women and children, in most cases, are family members of men who joined ISIS.